The Challenges of Transhumanism to Bioethics: Os Desafios do Transumanismo à Bioética - Camargo Brito, Ricardo; Ried, Nicolás (Acta Bioethica, 2024)
This article explores the challenges presented to bioethics by the emergence of transhumanism in the West. The exploration is approached from a genealogical research perspective. A genealogical investigation aims to question the conditions of intelligibility of transhumanism and from there analyze its impacts on the updating of a central debate in bioethics, namely: the limits to the manipulation of human life. Transhumanism, inhabiting the crisis of humanism that precedes and compels it, updates the issue of the human condition by presenting a line of argument that at least authorizes to formulate again the limit question: can we/should we go beyond the human?